‘I loved to be included’ (Proverbs 1:8–19): The Church and Tiv Christian Youth Development - Uroko, Favour C.; Enobong, Solomon (Hervormde teologiese studies, 2021)
This article examined the warning against evil companions in Proverbs 1:8–19 and the role of the church in addressing the involvement of Tiv youths in crime in Benue State and its implications for actions. Wicked people were zealous in seducing others into the paths of destruction. Would young people shun temporal and eternal ruin? This was the reason for Solomon’s instruction in Proverbs 1:8–19. He admonished his son with the caption ‘hear,’ which presented the son with a choice. However, Solomon implored the child to refuse to take any step in destructive paths of evildoers. The persuasive nature of the pericope was important in addressing the growing crime rate amongst Tiv youths in Benue State. Most youths in Tiv communities were being enticed into joining criminal gangs, secret cults and rituals in order to make quick wealth. Unfortunately, the number of youths in these immoral acts such as YahooYahoo amongst Tiv youths kept on increasing in the midst of the growing number of churches in most Tiv societies. Rhetoric analysis was used as the methodology. As part of recommendations, parents should instruct, discipline and stop their children from engaging in acts that lead to death. The youths should also avoid evil companions to avoid falling into trouble.Contribution: Youths are the leaders of tomorrow, which makes admonition to youths a necessity for the growth of the Tiv Society. Proverbs 1:8–19 provides roadmaps that Tiv leaders and the church could adopt in preserving morality among Tiv youths.